Influence of temperature gradients on the sound field in ice hockey halls - Pappa, Alexandra (My University, 2023)
This thesis studies the way that temperature gradients affect the sound field in ice hockey halls. This is achieved through reverberation time evaluation. The motivation behind this investigation is found in recent measurements in an ice hall. Substantial differences in reverberation times were observed when the hall was in operation in comparison to the hall without an established ice surface. The differences were mainly located in the low and middle frequency range. The aim of this thesis is to explore and identify the reasons behind this phenomenon. It is assumed to be linked to the temperature gradient, formed due to the presence of ice, that leads to refraction. To further investigate this hypothesis, new reverberation time measurements are carried out in three ice hockey halls. They are accompanied with air temperature measurements, to enable the temperature gradient estimation. Additionally, COMSOL Multiphysics® is used to simulate one of the halls in order to showcase the effects of refraction and calculate the reverberation time. Finally, measurement and simulation results are compared for the case with and without ice on the ground of the rink. Some conclusions are then drawn regarding the nature of the phenomenon and possible modifications are considered.
Keywords: reverberation time, ice hockey, T20, temperature gradient, room acous tics, geometrical acoustics, ray-tracing, refraction, COMSOL